Characteristics of lumbar canal stenosis patient at Koja district hospital year 2011-2021 - Nurfadhilah, Muhammad Iqbal; Priyamurti, Heka; Widodo, Arsanto Tri (International Journal of Advances in Medicine, 2022)
Background: Since there are too many cases of lumbar canal stenosis in Indonesia. The aim of the study was to discover all the factors that influence the incidence of lumbar canal stenosis. Methods: This study used all cases of lumbar canal stenosis in Koja District Hospital in Jakarta from 2011 to 2021. This was a medical record-based retrospective study in which files of patients with the diagnosis of lumbar canal stenosis were reviewed. A descriptive analytic test was used to analyze results was presented in the form of a table. Results: There were 48 lumbar canal stenosis cases in male patients out of 66 total patients. Incidents of lumbar canal stenosis occurred more frequently in anatomical locations L4-5 than in other locations. There were 48 lumbar canal stenosis cases with anatomical locations L4-5 in 50 patients from 66 patients. Incidents of lumbar canal stenosis occur in people with obesity more frequently than in people without obesity. There were 48 lumbar canal stenosis cases in people with obesity patients out of 66 total patients. The incidence of lumbar canal stenosis with a moderate VAS score was greater than that with a mild or severe VAS score. There were 48 lumbar canal stenosis patients with a moderate vas score out of 66 patients. There were 59 lumbar canal stenosis patients who got surgery out of 66 patients, and 7 of them had no surgery. Lumbar canal stenosis more frequently occurred in men than women, with more frequent anatomical lesions in L4-L5, and more frequently in people with obesity than in people without obesity. Most of them had a moderate VAS score and got surgery. Conclusions: According to this study, males had more lumbar canal stenosis incidents than females.